International pharmacy students’ role in translating an HIV and Aging survey from English to French, Spanish, and Vietnamese - Ware, Kenric (Journal of International Students, 2023)
International pharmacy students enhance the healthcare landscape through unique vantage points and diverse communication abilities. Their impact actualizes beyond pharmacy settings into community service arenas. This paper describes a collaboration between international pharmacy students and a statewide human immunodeficiency virus (HIV) needs assessment project in the United States (South Carolina). By translating a survey designed for people living with HIV from English to French, Spanish, and Vietnamese, the international pharmacy students reported greater familiarity with HIV nomenclature and treatment parameters. They also shared their paths to the United States and the importance of frequent use of non-English languages to their survey translations. The international pharmacy students viewed the survey’s lengthiness as a possible barrier to participation. Articulating these experiences may heighten awareness of the value international students embody along with motivate other international students to embrace moments that center their linguistic latitudes.